Strategi Influencer TikTok untuk Peningkatan Omzet UMKM Berbasis Etika Bisnis Islam - Izzatin Nabila; Romzatul Widad (TIN: Terapan Informatika Nusantara, 2026)
Information technology developments have driven social media adoption as a marketing tool for MSMEs. TikTok has proven effective in increasing sales, but its practices need to be examined from Islamic business ethics which prohibit gharar and tadlis and require honesty (shiddiq) and transparency (tabligh). Research integrating TikTok Influencer marketing effectiveness with Islamic business ethics remains limited. This study aims to analyze the effect of TikTok Influencer promotions on MSME Risoles Endul Kraksaan's revenue and review it based on Islamic business ethics. A mixed methods explanatory sequential design was used with 20 respondents (Spearman correlation) and in-depth interviews. Results showed a correlation coefficient of 0.676 (p=0.001), indicating a significant positive relationship between TikTok Influencer promotions and increased revenue. Daily revenue increased from IDR 1-1.7 million to IDR 2.5-3.5 million, equivalent to a monthly increase from IDR 30-51 million to IDR 75-105 million. Promotional practices have fulfilled the principles of shiddiq, tabligh, and are free from gharar and tadlis. The contribution of this research is an integrative model of Influencer marketing effectiveness with Islamic business ethics and an applicable framework for Muslim MSMEs in effective and sharia-compliant digital marketing strategies. This study is limited to one MSME and one platform. TikTok Influencer promotions significantly affect MSME revenue and align with Islamic business ethics.